Calcification in Human Intracranial Aneurysms Is Highly Prevalent and Displays Both Atherosclerotic and Nonatherosclerotic Types. Issue 10 (October 2019) - Gade, Piyusha S.; Tulamo, Riikka; Lee, Kee-won; Mut, Fernando; Ollikainen, Eliisa; Chuang, Chih-Yuan; Jae Chung, Bong; Niemelä, Mika; Rezai Jahromi, Behnam; Aziz, Khaled; Yu, Alexander; Charbel, Fady T.; et al.
Abstract : Objective: Although the clinical and biological importance of calcification is well recognized for the extracerebral vasculature, its role in cerebral vascular disease, particularly, intracranial aneurysms (IAs), remains poorly understood. Extracerebrally, 2 distinct mechanisms drive calcification, a nonatherosclerotic, rapid mineralization in the media and a slower, inflammation driven, atherosclerotic mechanism in the intima. This study aims to determine the prevalence, distribution, and type (atherosclerotic, nonatherosclerotic) of calcification in IAs and assess differences in occurrence between ruptured and unruptured IAs. Approach and Results: Sixty-five 65 IA specimens (48 unruptured, 17 ruptured) were resected perioperatively. Calcification and lipid pools were analyzed nondestructively in intact samples using high resolution (0.35 μm) microcomputed tomography. Calcification is highly prevalent (78%) appearing as micro (<500 µm), meso (500 µm–1 mm), and macro (>1 mm) calcifications. Calcification manifests in IAs as both nonatherosclerotic (calcification distinct from lipid pools) and atherosclerotic (calcification in the presence of lipid pools) with 3 wall types: Type I—only calcification, no lipid pools (20/51, 39%), Type II—calcification and lipid pools, not colocalized (19/51, 37%), Type III—calcification colocalized with lipid pools (12/51, 24%). Ruptured IAs either had no calcifications or had nonatherosclerotic micro- or meso-calcifications (Type I or II), without macro-calcifications. Conclusions: Calcification in IAs is substantially more prevalent than previously reported and presents as both nonatherosclerotic and atherosclerotic types. Notably, ruptured aneurysms had only nonatherosclerotic calcification, had significantly lower calcification fraction, and did not contain macrocalcifications. Improved understanding of the role of calcification in IA pathology should lead to new therapeutic targets. Abstract : Supplemental Digital Content is available in the text.